For hunger-proof cities : sustainable urban food systems - Koc̦, Mustafa (International Development Research Centre, 1999)
For Hunger-proof Cities is the first book to fully examine food security from an urban perspective. It examines existing local food systems and ways to improve the availability and accessibility of food for city dwellers. It looks at methods to improve community-supported agriculture and cooperation between urban and rural populations. It explores what existing marketing and distribution structures can do to improve accessibility and what the emerging forms of food-distribution systems are, and how they can contribute to alleviating hunger in the cities. Finally, the book discusses the underly.
"Most of the papers in this volume were presented at the International Conference on Sustainable Urban Food Systems ... at Ryerson Polytechnic University, Toronto"--Page 4
Keywords: Food supply -- Congresses.; Food supply -- Developing countries -- Congresses.; Nutrition policy -- Congresses.; Sustainable agriculture -- Congresses.; Urban health -- Congresses.; Aliments -- Approvisionnement -- Congrès.; Aliments -- Approvisionnement -- Pays en voie de développement -- Congrès.; Politique alimentaire -- Congrès.; Agriculture durable -- Congrès.; Santé urbaine -- Congrès.; TECHNOLOGY & ENGINEERING -- Food Science.; COOKING -- General.; Food supply; Nutrition policy; Sustainable agriculture; Urban health; Developing countries; Voedselvoorziening.; Stedelijke gebieden.; Electronic books.; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.